Relationship Between Diet and Incident Hypertyension in the Work Area Health Center Kabaena - Arafat Aljiihadi Hakim; Suarnianti; Liza Fauziah (Ammar Dharma Foundation, 2025)
Background: Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg, which is caused by disorders in the blood vessels that result in the supply of oxygen and nutrients carried by the blood being blocked to the body tissues that need it.Objective: The purpose of this study was to determine the relationship between diet and the incidence of hypertension in the Kabaena Health Center work area.Methods: uses a quantitative research type, descriptive design with a Cross Sectional approach. The population in this study were all people suffering from hypertension at the Kabaena Health Center, totaling 57 people. The sample in this study was 57 respondents using a sampling technique, namely total sampling. Measurement of variables using an instrument in the form of a Frequency Food Questionnaire (FFQ). Data management using SPSS. The analysis used was univariate analysis and bivariate analysis using the chi square test (ρ <0.05).Results: bivariate analysis showed a relationship between the type of food and the incidence of hypertension (ρ = 0.041), and no relationship between the amount and frequency of eating and the incidence of hypertension (ρ = 0.899, ρ = 0.245).Conclusion: The conclusion of this study is that there is a relationship between the type of food and the incidence of hypertension and there is no relationship between the amount and frequency of eating and the incidence of hypertension in the Kabaena Health Center work area.